2020
DOI: 10.1371/journal.ppat.1008970
|View full text |Cite
|
Sign up to set email alerts
|

E2 ubiquitin-conjugating enzyme UBE2L6 promotes Senecavirus A proliferation by stabilizing the viral RNA polymerase

Abstract: Senecavirus A (SVA), discovered in 2002, is an emerging pathogen of swine that has since been reported in numerous pork producing countries. To date, the mechanism of SVA replication remains poorly understood. In this study, utilizing iTRAQ analysis we found that UBE2L6, an E2 ubiquitin-conjugating enzyme, is up-regulated in SVA-infected BHK-21 cells, and that its overexpression promotes SVA replication. We determined that UBE2L6 interacts with, and ubiquitinates the RNA-dependent RNA polymerase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…SVA generally induces unobservable CPE on cell monolayers within 12 hpi, during which the virus-infected cells, however, underwent significant variation in several metabolic pathways, like carbon, purine and pyrimidine metabolisms, as evidenced by our recent report concerning proteomic profiling for SVA-infected cells (Liu et al, 2021b). SVA infection triggers a variety of metabolic and biochemical changes in its host cells through virus-specific or -nonspecific mechanisms (Fernandes et al, 2019;Hou et al, 2019;Wen et al, 2019;Li et al, 2020). Integrated omics can assist on deciphering complex networks in vitro or in vivo, and especially on unveiling the interaction among bio-relevant molecules to affect disease outcome (Rosa-Fernandes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…SVA generally induces unobservable CPE on cell monolayers within 12 hpi, during which the virus-infected cells, however, underwent significant variation in several metabolic pathways, like carbon, purine and pyrimidine metabolisms, as evidenced by our recent report concerning proteomic profiling for SVA-infected cells (Liu et al, 2021b). SVA infection triggers a variety of metabolic and biochemical changes in its host cells through virus-specific or -nonspecific mechanisms (Fernandes et al, 2019;Hou et al, 2019;Wen et al, 2019;Li et al, 2020). Integrated omics can assist on deciphering complex networks in vitro or in vivo, and especially on unveiling the interaction among bio-relevant molecules to affect disease outcome (Rosa-Fernandes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitin-mediated pathway is a specific protein degradation pathway that is tightly regulated in space and time. E2 ubiquitin-conjugating enzyme UBE2L6 promotes Senecavirus A proliferation by stabilizing the viral RNA polymerase ( 31 ). The production of type I IFNs are hindered by SARS-CoV-2 membrane protein through the degradation of TBK1 via ubiquitin-mediated processes ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that, although a relatively lower MOI of 0.5 than ours (MOI = 5) was used in this study, the cell samples used for the proteomic analysis were also collected at an early stage of SVA infection (6 hpi); however, this study did not analyze cell samples at other time points post-infection [ 10 ]. Similarly, Li and colleagues also showed that many innate immune-related proteins, such as Mx1, Mx2, ISG15, IFIT1, OAS1 and DDX58, were significantly upregulated in SVA-infected ST cells at 12 and 24 hpi by iTRAQ-coupled LC-MS/MS analysis, even though a different cell type and a lower MOI of 0.1 were used [ 43 ]. Furthermore, a transcriptome analysis also discovered that the innate immune-related genes and pathways were significantly activated in SVA-infected porcine renal proximal tubule epithelial cells (LLC-PK1) at 6 and 12 hpi, which were also in the early stage of SVA infection [ 44 ].…”
Section: Discussionmentioning
confidence: 99%